Study of Resistance Spot Welding Between AISI 301 Stainless Steel and AISI 1020 Carbon Steel Dissimilar Alloys - M., Ishak; L. H., Shah; I. S. R., Aisha; W., Hafizi; M. R., Islam (Universiti Malaysia Pahang, 2014)
Joining dissimilar metals has recently become very popular in industries because of the advantages associated with the weld joint. This paper focuses on an investigation of mechanical and material properties, and the optimization of mechanical properties in resistance spot welding methods in lap configurations between AISI 301 stainless steel and AISI 1020 carbon steel.The Taguchi method was used to design experiments. Welding was conducted using a spot welder. Tensile and Charpy impact test specimens were prepared from the welded sheets in appropriate dimensions and tensile and Charpy impact test s were performed for each specimen. The depth and width of weld nuggets were investig ated. It can be concluded from the investigation that the welding joint in this method can offer moderate strength and moderate Charpy impact energy. From the results of the Taguchi analysis, the combination of optimum parameters for dissimilar stainless s teel - carbon steel resistance spot welding is : welding current , 5.0kA ; welding squeeze time , 3.0 cycle ; and welding pressure , 40 psi. In order to improve significant mechanical and metallurgical properties of the joint, o ther variable parameters like voltag e, electrode tip diameter etc . can also be introduced and investigated so that the most influential parameters and their suitable ranges can be identified .